Observations on the Biology of Afrotropical Hesperiidae (Lepidoptera) with particular reference to Kenya. Part 11. Heteropterinae - Cock, Matthew J. W.; Congdon, T. Colin E. (Zootaxa, 2017)
Partial life histories from Kenya or Tanzania are presented for Metisella midas midas (Butler), M. medea medea Evans, M. orientalis orientalis Aurivillius, M. quadrisignatus nanda Evans, M. congdoni De Jong & Kielland and M. willemi Wallengren. The ovum of Metisella formosus linda Evans is also illustrated from Zambia. All feed on species of grasses (Poaceae). The convergence of the biology of the grass-feeding skippers, particularly Heteropterinae and Hesperiinae, Baorini is discussed.